Business and Human Trafficking: A Social Connection and Political Responsibility Model. Issue 2 (February 2021) - Van Buren, Harry J.; Schrempf-Stirling, Judith; Westermann-Behaylo, Michelle
Human trafficking is one of the most lucrative international criminal activities and is widespread across a variety of industries. The response to human trafficking in corporate supply chains has been dominated by analyses of due diligence obligations. Existing scholarship, however, has cast doubt on the effectiveness of corporate due diligence in addressing human trafficking, because human trafficking is the outcome of macro-level social structures that are created by and consist of multiple actors, including business. The outsourcing and sub-contracting model provides incentives throughout the global supply chain to sub-contract further to reduce the cost of labor, which has led to human trafficking remaining a pervasive problem. Business responsibility for human trafficking derives from the fact that business decisions and strategies enable the conditions that allow for human trafficking to occur within their supply chains. To address human trafficking, we propose a social connection and political responsibility model, based on Iris Marion Young's analysis of social connection and structural injustice, that is holistic, forward-looking, and outcomes-oriented. We differentiate between businesses with a strong connection to human trafficking and businesses with a weak connection, and within this distinction delineate different pathways that firms can take to meet their political responsibilities to address human trafficking. We conclude with implications for future research.